Coconut (Cocos nucifera)-based farming system: a viable land use option for small and marginal farmers in coastal Odisha - BHOL, N; SARANGI, S K; BEHERA, U K (The Indian Journal of Agricultural Sciences, 2015)
An investigation was carried out during 2012-2013 in Puri district of Odisha to study the composition, structure and role of coconut (Cocos nucifera L.) based farming in 15 different holding sizes, i.e. 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 and 1.5 acre. The experiment was laid out in randomised block design with three replications. The smaller holdings were found close to houses as homegardens and comparatively larger holdings were found little away from the houses. The composition was found very diverse consisting of perennial trees, annual crops and seasonal crops. The coconut based agroforestry systems of various sizes are playing important role for the household which include productive role, protective and ameliorative role, recreational and educational role as well as developmental role giving various kinds of tangible and intangible benefits. As the natural forest cover is less in coastal Odisha, a substantial quantity of fuel wood was found to be derived from homegarden and the contribution of fuel wood production increased with increase of holding size up to 1.2 acre. The net return varied from Rupees 5 617 to Rupees 32 850/annum showing the income level increased with increase in holding size, while the economics was calculated on acre basis, the net income ranged from Rupees 56 167 to Rupees 21 900 indicating decreasing trend towards higher holding sizes. In terms of market orientation, the smaller unit sizes were found more subsistence and less commercial than bigger holding sizes and vice versa. The coconut based agroforestry system of size 0.8 acre (perennials-coconut, siris, rain tree, eucalyptus, acacia, areca nut, mango, sissoo, teak, jackfruit, bamboo, guava, pomegranate, papaya, drumstick, bael, citrus, banana, curry leaf ; seasonals-pine apple, yam, arrowroot, turmeric, ginger, brinjal, okra, bitter gourd, ridge gourd, chilli, greens, cowpea, tomato, cauliflower, pumpkin; mushroom-paddy straw/oyster; fish- rohu, silver crap, grass crap; cattle, buffalo, goat, poultry, duck) was found to be the best among the holding sizes studied with regard to viability of landuse.